Politics of Law Legislation of Qanun Sharia Islam in the Province of Aceh, Indonesia - Hasnul Arifin Melayu; Md. Zawawi bin Abu Bakar; Norruzeyati binti Che Mohd Nasir (Law Department, Sharia and Law Faculty., 2019)
AbstractThis paper discusses the regulation in The Province of Aceh, which is related to the Islamic sharia law regarding the prohibition of seclusion, the so-called Qanun Khalwat. This writing looks at the initial socio-political conditions underlying the Qanun legal process as well as the effects of external pressure arising during this legislating process. This study aims to understand to what extent the Qanun Khalwat legislating process refers to the prevailing legal standards in Indonesia. The data in this paper were collected from interviews with several informants such as civil servants of the Aceh Islamic Sharia Department, Legal Bureau, and academics. Some information is also obtained through archive review. It found that the Qanun Khalwat legal process does not follow the standard formulation of national law because several conditions are not implemented in the legislating process, such as the lack of public participation during the process. Besides, there are still some texts in the qanun that are not standardized and are not suitable for use as formulations in qanuns.Keywords: Politics of law, Legisltaion, Qanun Khalwat, Aceh